FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL DALAM PERUSAHAAN MANUFAKTUR TAHUN 2015-2017. (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Arizta Rahmawati, 15.05.52.0022; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2019)
This study aims to determine and analyze the effect of profitability, firm size, business risk, sales growth and asset structure on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The data used in this study are data of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2015-2017. The method in selecting samples in this study uses a purposive sampling method with the aim of getting samples that are suitable with the purpose of the study. Based on these criteria, 204 samples were obtained. The hypothesis in this study was tested using a multiple linear regression analysis methods. The results of this study indicate that: (1) there is a significant influence between profitability on capital structure, (2) there is no significant effect between firm size on capital structure, (3) there is a significant influence between business risk on capital structure, (4) There is a significant influence between sales growth on capital structure, (5) there is no significant influence between asset structure and capital structure.